ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DALAM MENENTUKAN HARGA JUAL DENGAN METODE COST PLUS PRICING DENGAN PENDEKATAN FULL COSTING - Bosta Sihombing (DINAMIS, 2018)
The study entitled analysis of calculation of cost of goods Production in determining the sale price with the method of Cost Plus Pricing with Full Costing approach (case study on CV. Lembakalando Sentani, Jayapura, Papua). The purpose of this research is to know the calculation of cost of goods production and the process of determination of the sale price of the product on a CV. Lembakalando. Calculation of cost of goods produski by using the method of full costing and determination of the sale price by using a cost plus pricing. This type of research is a type of quantitative research .Characteristics based on the issues raised by the researcher, so this research is quantitative descriptive research is classified as. The data used in this study i.e., primary data obtained directly from the data companies such as interviews with the company as well as the data in the form of information fee-the cost of production of the company during the month of June 2017 and documentation. As for the secondary data obtained from books, journals, internet or other media that supported this research. From the results of data analysis, the results showed that the calculation of cost of goods production company 7 product the same as the calculation of cost of goods production by using method 1 full costing of products that the company's production of staple prices calculation lower than the calculation of cost of goods production full costin, and 2 the calculation of the product cost of goods production company than the calculation cost of goods production of full costing. This is because the cost of goods companies did not do a calculation of the children compared to full costing. In addition, the determination of the sale price of the company just did a calculation of the selling price estimation produkdengan level marked up by 10%, where the calculation of the sale price of the company on 1 type of product is lower than the cost plus method is pricingii, type 7 the company's calculation of product equal to the calculation method of cost plus pricing, and 2 types of products is higher than the company's calculation of calculation methods of cost plus pricing. So, the determination of the sale price must be done precisely because the selling price that is too high will make its products less competitive, whereas the selling price that is too low will cause losses for the company.